2018
DOI: 10.32601/ejal.460583
|View full text |Cite
|
Sign up to set email alerts
|

Prospective ESL/EFL Teachers’ Perceptions towards Writing Poetry in a Second Language: Difficulty, Value, Emotion, and Attitude

Abstract: The study aims to explore how 18 M.A. TESOL students, who are prospective or experienced ESL/EFL teachers, perceive poetry writing in a second language. A qualitative interview-based design was utilized. Following Iida's (2012a) analytical framework in examining EFL students' perceptions toward writing haiku in English, this current study investigates 18 prospective ESL/EFL teachers' perspectives through the lens of difficulty, value, emotion, and attitude. In order to validate the coding of the interviews, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Unfortunately, poetry was not favored because it was considered too difficult for students (Chamcharatsri, 2013;Dilidüzgün, 2015). Interestingly, a study by Liao and Roy (2017) found that the more exposure students had to poetry, the less their interest and confidence in poetry writing. However, in another context, Liao (2018) found that the negative feelings toward poetry surfaced only at the beginning of a course.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, poetry was not favored because it was considered too difficult for students (Chamcharatsri, 2013;Dilidüzgün, 2015). Interestingly, a study by Liao and Roy (2017) found that the more exposure students had to poetry, the less their interest and confidence in poetry writing. However, in another context, Liao (2018) found that the negative feelings toward poetry surfaced only at the beginning of a course.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a study by Liao and Roy (2017) found that the more exposure students had to poetry, the less their interest and confidence in poetry writing. However, in another context, Liao (2018) found that the negative feelings toward poetry surfaced only at the beginning of a course. The longer students dealt with their emotions through poetry, the more positive they viewed it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of poetry in EFL classroom is able to maintain students' interest to read and write (Beymer et al, 2020;Freyn, 2017). Poetry is able to provide emotion in language learning which give significant effect on students speaking and writing skills (Hirsch & Macleroy, 2020;Liao, 2018;Seltzer, 2020). By exposing students with poetry, it makes students become more creative in composing their own poetry (Cushing, 2018;Iida & Chamcharatsri, 2020).…”
mentioning
confidence: 99%
“…Speaking is considered as challenging language skills since it requires the development of other language aspects such as vocabulary, grammar, and pronunciation as well as other aspects such as confidence (Burns, 2019;Husnu, 2017;Tomak, 2021). Therefore, the use of poetry is effective in developing the language and non-language aspects that contribute to the improvement of students speaking skill (Hirsch & Macleroy, 2020;Liao, 2018). It is motivated by emotion and expression provided in the poetry which enable students to enjoy the learning process (Iida & Chamcharatsri, 2020;Sigvardsson, 2020).…”
mentioning
confidence: 99%